Analysis of the Role of the Prosecutor's Office in Utilizing Civil Law Instruments to Optimize the Recovery of Corrupt Assets - sudarto, sudarto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study examines the critical role of the Prosecutor's Office in employing civil law instruments to enhance the recovery of assets acquired through corrupt activities. Given the detrimental impact of corruption on national integrity and finances, efficient asset recovery is essential for restoring public trust and ensuring accountability. Through a qualitative analysis that includes case studies, legal frameworks, and interviews with key stakeholders, the research identifies various civil law tools utilized by the Prosecutor's Office, such as civil lawsuits, asset seizure, and restitution claims. The findings reveal that while the Prosecutor's Office possesses significant authority and resources to pursue civil actions, several challenges hinder optimal performance, including inadequate legal frameworks, resource constraints, and inter-agency coordination issues. The paper concludes by advocating for legislative reforms, enhanced training for prosecutors, and improved collaboration among law enforcement agencies to strengthen the effectiveness of asset recovery efforts in combating corruption.